Numerical prediction of strength and temperature changes within cemented paste backfill considering barricade stability - Di Wu; Liang Liu; Erol Yilmaz; Shilong Zheng (Engineering Science and Technology, an International Journal)
Manufacturing an intended recipe of tails, binder and water, cemented paste backfill (CPB) is employed to refill the cavities created in underground mining operations. To ensure that it remains stable and forms a solid structure, filling slurry must be supported by a rigid barricade at the bottom of the mining area. Fill structures’ process is guided via coupled thermal/hydraulic/mechanical/chemical developments, which can directly affect the stability of barricade. Hence, it is essential to study the pressure changes and distribution within the barricade. A fully coupled THMC numerical model was established in the current study in order to predict mechanical features and temperature changes inside CPB, and to measure effect of these changes on barricade’s stability. Predictive outcomes obtained from the model built were compared with the results of a field experiment, showing good consistency and thus proving model’s validity in mimicking evolution of temperature change and its effect on strength features of barricade in the course of backfill hydration. The verified multi-physical field model was used to numerically study the change of lateral pressure of barricade under different working conditions. The results show that properly increasing the initial temperature of CPB and increasing the distance between the barricade and the stope can effectively alleviate the lateral pressure on the barricade. The consequences of the existent research could offer a vital guideline on the topic of backfill barricade’s stability analysis.